2017
DOI: 10.1111/ddi.12600
|View full text |Cite
|
Sign up to set email alerts
|

Railway lines affect spatial turnover of pollinator communities in an agricultural landscape

Abstract: AimLandscape composition and spatial configuration of habitat patches are important determinants of biodiversity in fragmented semi‐natural habitats spread across agricultural landscapes. However, little attention has been paid to man‐made structures that can moderate spatial processes affecting pollinator communities. In a large‐scale study, we explored the importance of railway embankments for the turnover of pollinator species in agricultural landscapes. Because species differ in vulnerability to landscape … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…In homogenous intensive agricultural landscapes, such features may be the only locations where species survive (Wynhoff et al 2011). Van Geert et al (2010) and Moroń et al (2017) revealed that such linear habitats may function as biological corridors by facilitating the dispersal of insects and insect-pollinated plants. Railway embankments may increase the alpha diversity and community turnover of invertebrates and plant taxa (Moroń et al 2014, 2017; Vandevelde and Penone 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In homogenous intensive agricultural landscapes, such features may be the only locations where species survive (Wynhoff et al 2011). Van Geert et al (2010) and Moroń et al (2017) revealed that such linear habitats may function as biological corridors by facilitating the dispersal of insects and insect-pollinated plants. Railway embankments may increase the alpha diversity and community turnover of invertebrates and plant taxa (Moroń et al 2014, 2017; Vandevelde and Penone 2017).…”
Section: Introductionmentioning
confidence: 99%
“…As opposed to reference grasslands, patches located next to roads are connected with other grasslands adjacent to roads via road verges. These marginal habitats may improve species turnover among grasslands located near roads or even be a species pool for butterflies, enhancing patch colonization after some disturbances connected with grassland management ( Tikka, Högmander & Koski, 2001 ; Brunzel, Elligsen & Frankl, 2004 ; Moroń et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…In homogeneous landscapes, these marginal areas may be a habitat surrogate crucial for the survival of populations of endangered species. Such areas function often as movement and dispersal corridors or stepping stones in inhospitable matrix as pollinators rely on food and nesting sources that have patchy distribution (Kajzer-Bonk et al 2016 ; Moroń et al 2017 ). The positive effect of proximity of other windmills on wild bee diversity index and butterfly abundance indicates that at least for some species windmills may increase population connectivity in a landscape.…”
Section: Discussionmentioning
confidence: 99%
“…Such specific conditions may cause the formation of new species assemblages (Lundholm and Richardson 2010 ; Lenda et al 2012 ). There is growing evidence that highly transformed and degraded patches, like quarries, railway embankments, or road verges, can paradoxically become a surrogate habitat for many species including those of high conservation status, when their natural habitats disappear in agricultural landscapes (Beneš et al 2003 ; Heneberg et al 2012 ; Lenda et al 2012 ; Moroń et al 2014 , 2017 ; Berg et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%